RANCANG BANGUN APLIKASI UTS IN ME BERBASIS ANDROID MENGGUNAKAN FLUTTER DENGAN METODE RAPID APPLICATION DEVELOPMENT - I Made Widiarta; M Julkarnain; Jati Imanulloh (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Sumbawa University of Technology or commonly abbreviated as UTS is one of the campuses in Indonesia that is able to take advantage of technological advances, one of which is in the field of Information Technology. Every year UTS accepts hundreds to thousands of new student candidates. Every time the UTS RESPEK event is held, on the first day the committee will distribute booklets to prospective new students who take part in the activity. The budget for printing the booklet is very large, amounting to 30 million rupiah. This study aims to digitize the contents of the booklet in order to minimize the budget. This research uses a mixed approach, and the software development method used is the SDLC (System Development Life Cycle) RAD (Rapid Application Development) model and the beta testing application testing method. The modeling process uses an object-oriented approach and utilizes UML as a tool for application development. The conclusion of this study is to produce an Android-Based UTS IN ME Application that is able to make it easier for students to access basic information about the Sumbawa University of Technology campus.